Comparison of Natural Multipotent Stem Cell and Induced Pluripotent Stem Cell Therapeutic Applications: Benefits and Challenges - Wang, Fu Nan; Wang, Sebo Gene; Hsu, Ming Chu; Wang, Sebo Ling; Wang, Sebo Dih (Medical Research Archives, 2025)
Natural Multipotent Stem Cell preparation is unique and safe when compared with other methods. Using this technology, American Stem Cell Base Dr. Wang has treated more than 100 kinds of diseases, made thousands of transplantations, with excellent cure rate (> 90% cured or great improvement per clinical end point measurement) and most importantly, there are no significant side effects. In 2012, the Nobel Prize-winning medical technology, Induced Pluripotent Stem Cell, invigorated stem cell research as it showed that Induced Pluripotent Stem Cell has the potential to produce every type of cell and tissue in the body. However, the inherited properties of Induced Pluripotent Stem Cell were known as tumorigenicity, immunogenicity, and heterogeneity. In his 2024 review article, Dr. Yamanaka indicated that he had dedicated two decades of research aimed at overcoming these three difficulties. Given the potential for these cells to become cancerous stem cells, the widespread application of the technology in treating various clinical diseases might require collaborative research by scholars, scientists, and clinicians and potentially could take decades to resolve. Natural Multipotent Stem Cell, on the other hand, is a mature biotechnology with specialized technologies and capabilities for mass production. It has successfully treated over 100 long-standing and intractable diseases, potentially providing widespread relief to millions afflicted with these diseases. This study provided a side-by-side comparison of two leading and promising stem cell therapy candidates, natural Multipotent Stem Cell and Induced Pluripotent Stem Cell, in clinical applications and present the challenges and promises in stem cell therapy.